PERFORMANCE AND KINETICS OF AN INTEGRATED SUSPENDED AND SUBMERGED ATTACHED GROWTH BIOREACTOR TREATING INDUSTRIAL WASTEWATER - EZECHI, EZERIE HENRY (2016)
Biological wastewater treatment technology is an aged long ctTective method associated with numerous advantages in tem1s of operational cost. However, conventional biological wastewater treatment technologies are also associated with demerits such as large space requirement due to the segregated compartments.